TGF-β1 Exerts Opposing Effects on Grass Carp Leukocytes: Implication in Teleost Immunity, Receptor Signaling and Potential Self-Regulatory Mechanisms - Yang, Mu; Wang, Xinyan; Chen, Danyan; Wang, Yanan; Zhang, Anying; Zhou, Hong (PLOS ONE, 2012)
In fish immunity, the regulatory role of transforming growth factor-β1 (TGF-β1) has not been fully characterized. Here we examined the immunoregulatory effects of TGF-β1 in grass carp peripheral blood leukocytes (PBL) and head kidney leukocytes (HKL). It is interesting that TGF-β1 consistently stimulated the cell viability and the mRNA levels of pro-inflammatory cytokines (Tnfα and Ifnγ) and T/B cell markers [Cd4-like (Cd4l), Cd8α, Cd8β and Igμ] in PBL, which contrasted with its inhibitory tone in HKL. Further studies showed that grass carp TGF-β1 type I receptor, activin receptor-like kinase 5 (ALK5), was indispensable for the immunoregulatory effects of TGF-β1 in PBL and HKL. Notably, TGF-β1 persistently attenuated ALK5 expression, whereas immunoneutralization of endogenous grass carp TGF-β1 could increase ALK5 mRNA and protein levels. It is consistent with the observation that TGF-β1 decreased the number of ALK5+ leukocytes in PBL and HKL, revealing a negative regulation of TGF-β1 signaling at the receptor level. Moreover, transient treatment with TGF-β1 for 24 h was sufficient to induce similar cellular responses compared with the continuous treatment. This indicated a possible mechanism by which TGF-β1 triggered the down-regulation of ALK5 mRNA and protein, leading to the desensitization of grass carp leukocytes toward TGF-β1. Accordingly, our data revealed a dual role of TGF-β1 in teleost immunity in which it can serve as a positive or negative control device and provided additional mechanistic insights as to how TGF-β1 controls its signaling in vertebrate leukocytes.